Comparative studies on sulfosate and glyphosate - Rajan, A. (2014)
The close structural similarity between sulfosate and glyphosate makes comparative evaluation of their effectiveness difficult both in glasshouse and field experiments. In three experiments on lalang, sulfosate was equal in effectiveness compared to glyphosate, while in one study if proved to be superior. Analysis of leaf chlorophyll content showed significantly lower levels during the first two weeks in all sulfosate treated lalang plants. This reduction was dose dependent and was reflected in reduced biomass production and regrowth potential in one of four studies conducted. The response in chlorophyll levels clearly indicate an early or more rapid initial uptake and activity and that the effect of sulfosate is different from glyphosate. Sulfosate also showed a higher degree of effectiveness when ca 4 mm rain occured within the two first hours of spraying,with sulfosate treated plants having lower fresh weights at five weeks after treatment and less regrowth compared to glyphosate. In certain situations the faster action could offer some degree of rainfastness and better control in favour of sulfosate.